The Perception of Psychosocial Risks and Work-Related Stress in Relation to Job Insecurity and Gender Differences: A Cross-Sectional Study. (19th December 2018) - De Sio, Simone; Cedrone, Fabrizio; Trovato Battagliola, Edoardo; Buomprisco, Giuseppe; Perri, Roberto; Greco, Emilio
Abstract : Introduction . The perception of psychosocial risks exposes workers to develop work-related stress. Recently the attention of scientific research has focused on a psychosocial risk already identified as "job insecurity" that regards the "overall concern about the continued existence of the job in the future" and that also depends on worker's perception, different for each gender. Aim of the Study . The aim of this cross sectional study is to show if job insecurity, in the form of temporary contracts, can influence the perception of psychosocial risks and therefore increase worker's vulnerability to work-related stress and how the magnitude of this effect differs between genders. Materials and Methods . 338 administrative technical workers (113 males and 225 females) were administered a questionnaire, enquiring contract typology (permanent or temporary contracts), and the Health Safety Executive questionnaire to assess work-related stress. The Health Safety Executive Analysis Tool software was used to process collected questionnaires and the Wilcoxon rank-sum test was used to evaluate the statistical significance of the differences obtained. Results. Workers with temporary contracts obtained lower scores than workers with permanent contracts in all the domains explored by the Health Safety Executive Analysis questionnaire, statistically significant (P<0, 05). The female workers obtained lower scores than male workers in all domains explored by the Health Safety Executive questionnaire. Conclusions. Authors conclude that perception of psychosocial risks can be influenced by job insecurity, in the form of temporary contracts, and increases worker's vulnerability to work-related stress and differs between genders.